The Impact of Traditional Acehnese Games on Physical Fitness, Motivation, and Social Skills among Male Students Participating in Extracurricular Football Activities at MTs Negeri 5 Bireuen - Bangkit Budi Iswanjaya; Ari Iswanto; Ghozi Indra Waskita; Dewangga Yudhistira (Global Sustainability Research Institute, 2026)
Introduction: Traditional games are part of local cultural heritage that have the potential to support physical, motivational, and social development in students. In physical education contexts, integrating traditional games may provide an enjoyable learning experience while enhancing students’ physical fitness and social character. Methods: This study employed a quasi-experimental method using a randomized control group pretest–posttest design. A total of 26 male students participating in soccer extracurricular activities were selected through total sampling and divided into experimental and control groups. Research instruments included the Indonesian Physical Fitness Test (TKJI), a learning motivation questionnaire, and a social skills questionnaire (SSRS). Results: The findings indicate that the implementation of traditional Acehnese games led to improvements in students’ physical fitness, learning motivation, and social skills. Students who participated in traditional game-based activities demonstrated better physical condition, higher motivation to engage in learning activities, and more positive social interactions compared to those who did not receive the treatment. Conclusion and Suggestion: This study concludes that traditional Acehnese games are effective as an alternative learning strategy to enhance physical fitness, motivation, and social skills among students in extracurricular sports activities. It is recommended that physical education teachers and schools incorporate traditional games into extracurricular and instructional programs to promote holistic student development. Future research is encouraged to involve larger samples and different educational levels to strengthen the generalizability of the findings.